Validação do método de geoprocessamento na estimativa de perdas de solo por erosão laminar, em pequenas propriedades rurais, pela comparação com o método a campo - Moura, Jaqueline de (2022)
The soil loss by erosion can result in irreversible negative environmental impacts. Soils with historic of misuse, without any conservation practices application, are increasingly susceptible to major nutrient and organic matter losses, besides the loss of all the structure that allow the plant development and, consequently, human. The geoprocessing combine with the Universal Soil Loss Equation (USLE), can be an important tool to predict soil losses. The purpose of this study is to verify if the soil loss by laminar erosion estimate data, using geoprocessing method are like the data obtained by the field method, to make the technical evaluation faster and more practical. For this, a tutorial used to determine soil losses by laminar erosion in watersheds was adapted. The work was carried out in seven small properties, located in the Quatorze River Basin, in the Brazilian municipality of Francisco Beltrão, State of Paraná. The software used for the geoprocessing method was the SPRING. As a result, it was verified that the data obtained by the field method were inserted within the intervals obtained by the geoprocessing. Thus, it is suggested that the geoprocessing method, using the tutorial adapted for this work, can be an alternative tool for estimating soil losses by laminar erosion in the field, minimizing the time and cost of this process. Furthermore, using the geoprocessing method, it is possible to carry out simulations that provide the technician with subsidies for decision making regarding the use of the area, aiming at minimizing soil losses due to erosion.